Influence of Hydrogen Peroxide on Mineralization in Dental Pulp Cells: A Systematic Review - Reis-Prado, Alexandre Henrique dos; Grossi, Isadora Rodrigues; Chaves, Hebertt Gonzaga dos Santos; André, Carolina Bosso; Morgan, Luís Fernando dos Santos Alves; Briso, André Luiz Fraga; Cintra, Luciano Tavares Angelo; Benetti, Francine (Frontiers in Dental Medicine, 2021)
Background: Dental bleaching agents show the ability to permeate through dental hard tissues, which may lead to pulp tissue changes. This systematic review (PROSPERO register: CRD42020213767) is aimed at understanding the effects of bleaching agents on the process of mineralization of the pulp tissue. Methods: Only in vitro studies evaluating the influence of hydrogen peroxide (HP) on mineralization in dental pulp cells were included. Studies without a non-bleached control group or cells after co-treatment with a bleaching agent other than HP and/or carbamide peroxide were excluded. The primary outcomes evaluated were alkaline phosphatase (ALP) activity and mineralized nodule deposition. The mineralization markers analysis in dental pulp cells and the cell viability were considered secondary outcomes. Two independent authors conducted a systematic search (PubMed/MEDLINE, Scopus, Embase, Cochrane Library, and OpenGrey until January 2021) with no language restrictions and performed data extraction. The quality assessment was appraised according to a modified Joanna Briggs Institute critical appraisal checklist. Results: The search resulted in 473 studies, and 11 were considered eligible. Overall, a reduction in the process of mineralization was observed among pulp cells after bleaching. A reduction in the ALP activity was reported in the mostly bleached groups using different protocols and analysis periods of nine studies. Regarding mineralized nodule deposition, 6 studies reported a significant reduction from 7 to 21 days among bleached groups. Of those three studies that investigated other mineralization markers, two found a reduction in the expression of dentin matrix acidic phosphoprotein (DMP)-1, dentin sialophosphoprotein (DSPP), and matrix extracellular phosphoglycoprotein (MEPE) among some bleaching gel concentrations. In contrast, one study showed a greater expression of osteopontin (OPN) and osteocalcin (OCN) in 100 μmol/L HP after 5 or 10 min of exposure, and another study showed significant induction of DSPP in concentrations of up to 0.5 mmol/L HP. Conclusion: Especially, high concentrations of bleaching gel reduce the potential of mineralization in pulp cells in in vitro studies; however, different HP concentrations, bleaching protocols, and analysis periods can influence this outcome.